Homeostatic Disorders in Acute Poisoning by Psychotropic Agents - M. V. Belova; K. K. Ilyashenko; T. V. Yermokhina; Ye. A. Luzhnikov; B. V. Davydov; S. B. Matveyev (Общая реаниматология)
Objective: to determine the impact of the degree of oxidative stress on homeostatic parameters in critically ill patients with acute poisoning by psychotropic agents (PTA).Materials and methods. The components of lipid peroxidation (LPO) and the antioxidative system (AOS), blood rheological and immunological parameters, and the markers of endogenous intoxication were studied in 43 patients with severe acute PTA intoxication before and during intensive detoxification therapy.Results. The first hours of poisoning were marked by LPO-AOS imbalance with a significant preponderance of peroxidation processes, by impaired blood viscous properties, the manifestations of secondary immunodeficiency and endogenous intoxication. There were changes in the study parameters during detoxification therapy and at the early somatogenic stage of the disease.Conclusion. In patients with acute poisoning-induced critical conditions, the degree of oxidative stress affects the time course of homeostatic changes and determines the severity of endotoxicosis at all stages of the disease.